PENERAPAN STRATEGI PEMBELAJARAN PRAKTIK IBADAH MULTI MAZHAB DAN RELEVANSINYA TERHADAP PEMBANGUNAN SEMANGAT PLURALISME DI MAHASISWA PRODI PAI FITK UINSU TA 2021-2022 - Ihsan Satrya Azhar (Jurnal Al-Fatih, 2022)
The background of this research is that in teaching of the worship practice subject, there should be a value of sense of plurality among the society, especially in Fiqh, thorough a content of Multi madzhab and teaching strategy. thorough The use of both things in teaching and learning , the sense of plurality can be achieved. The two problems used in this research, are the contents of teaching comes from one or various school or madzhab in fiqh and how it implemented to achive the purpose of teaching and learning goal. It is expected that the results of this research can be used as a parameter for both teaching and learning goal and a continuity of Worship Practice subject. This is a qualitative-descriptive research conducted in Islamic Education Departement of Education and Teaching Faculty of State of Islamic University of North Sumatra. The data were collected using the method of observation, interview, anddocumentation. The data analysis was conducted by giving the meaning of thedata that have been collected. From these meanings, a conclusion was drawn. Thedata validity was examined through triangulation including sources, technique,time and theory. The results of this research showed that thorough a content of Multi School of Fiqh, and its teaching strategy the sense of plurality can be achieved.